2008
DOI: 10.1542/peds.2008-1315o
|View full text |Cite
|
Sign up to set email alerts
|

Infant Sleeping Arrangements and Practices During the First Year of Life

Abstract: OBJECTIVES. Our goal was to examine the sleeping arrangements for infants from birth to 1 year of age and to assess the association between such arrangements and maternal characteristics.METHODS. Responses to the 3-, 6-, 9-, and 12-month questionnaires from the Infant Feeding Practices Study II were analyzed to assess sleep arrangements, including bed sharing, the latter defined as mother ever (in a given time frame) slept with the infant on the same sleeping surface for nighttime sleep. Women were also asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 22 publications
10
87
1
Order By: Relevance
“…Our data are similar to those by Hauck et al 27 who reported that 85% of their infants slept in the same room as their mother, but at 12 months the rate was 29%; in our study it remained high, at around 54%. We found that co-sleeping was present in approximately 10% of infants at 3-6 months with a gradual increase to 18% at 9 and 12 months.…”
Section: Sleeping Arrangementssupporting
confidence: 92%
“…Our data are similar to those by Hauck et al 27 who reported that 85% of their infants slept in the same room as their mother, but at 12 months the rate was 29%; in our study it remained high, at around 54%. We found that co-sleeping was present in approximately 10% of infants at 3-6 months with a gradual increase to 18% at 9 and 12 months.…”
Section: Sleeping Arrangementssupporting
confidence: 92%
“…17 In addition, infant comfort, which includes longer sleep duration, is a priority for many parents, and this goal often results in prone and side positioning 18 -26 and sharing of sleep surfaces. 27,28 Health care providers should be aware of these influences on parental decisionmaking so that appropriate guidance can be given.…”
Section: Discussionmentioning
confidence: 99%
“…142,252,253 Breastfeeding is a common reason given by mothers for bed-sharing with their infants. 254 Studies have found an association between bed-sharing and longer duration of breastfeeding, but their data cannot determine a temporal relationship (ie, it is not known whether bed-sharing promotes breastfeeding or if breastfeeding promotes bed-sharing, or if women who prefer 1 practice are also likely to prefer the other). 255 Although bed-sharing may facilitate breastfeeding, it is not essential for successful breastfeeding.…”
Section: If a Breastfeeding Mother Brings The Infant Into The Adult Bmentioning
confidence: 99%